PENGARUH CITRA MEREK DAN PENGALAMAN PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN ULANG GENERASI Z DENGAN KEPERCAYAAN MEREK SEBAGAI VARIABEL MEDIASI - Mumtaz, Nabila; Purwanto, Edy (Journal MISSY (Management and Business Strategy), 2025)
The cosmetics industry in Indonesia has experienced significant growth in recent years, even so consumers must remain smart in choosing cosmetic products. This study aims to examine the effect of brand image and customer experience on generation Z's repurchase intention in Sumenep Regency through brand trust. This research was conducted on Pinkflash cosmetic products. This study used purposive sampling method as a sampling technique and obtained a sample size of 108 respondents. The testing technique used in this research is PLS-SEM. The results showed that brand image, customer experience, and brand trust have a direct influence on repurchase intention. Meanwhile, brand image does not influence repurchase intention through brand trust, but customer experience affects repurchase intention through brand trust.